Factors influencing the purchasing intention of Takaful hibah products; a conceptual framework / Faziatul Amillia Mohamad Basir and Muhammad Abd Hadi Abd Rahman - Mohamad Basir, Faziatul Amillia; Abd Rahman, Muhammad Abd Hadi (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
The upward trends of frozen assets and remaining unsolved become worrying as the inheritance assets are not efficiently utilized. One of the root causes of frozen assets in Malaysia is the lack of awareness of estate planning among individuals, particularly the Muslim community. The increasing frozen assets were contributed by the low penetration of estate planning among individuals, making the estate administration process even abandoned. Takaful hibah has been introduced as one of the Shariah-compliant products made accessible by Islamic Financial Institutions (IFIs) to overcome these issues. Its versatility is proven in risk management, mitigation, and wealth management, especially in estate planning. Integrations of takaful and hibah have provided reduced time and cost consumption for the inheritance process for Muslims in Malaysia. Further, past research on estate planning related to takaful hibah is still limited to the aspect of consumer purchasing intentions on takaful hibah. Therefore, this paper aims to determine the relationship between attitude, subjective norms, perceived behavioral control, and knowledge towards the intention to purchase takaful hibah. Findings in this study perhaps will focus on twofold contributions. First, it directs the takaful hibah operators to enhance their marketing efforts, such as more product awareness towards the Muslim working adults’ population. Second, regarding academics, this finding helps boost education programs by stimulating the attitude to purchase the takaful hibah. Hence, our study contributes to filling the knowledge gaps on the takaful hibah, as one of the Islamic estate planning tools, particularly among Muslims in Malaysia.